Ultra-sensitive pH responsive hydrogels with injectable and self-healing performance for controlled drug delivery - Yu, Yang; Zhao, Yili; Zou, Yujiao; Lu, Chanyi; Li, Ni; Shi, Zhiyuan; Li, Xin; Lai, Xixi (International journal of pharmaceutics: X, 2025)
Ultra-sensitive pH-responsive drug delivery system designed to operate within the slightly acidic microenvironment of tumors are highly desired for hydrogel applications in cancer therapy. In this study, 4-Formylbenzoic acid modified polyvinyl alcohol (PVA-FBA, PF) was synthesized and utilized as a carrier for encapsulating the anticancer drug Doxorubicin (Dox). This was subsequently crosslinked with polyethylenimine (PEI) via benzoic-imine bond to form drug-loaded PVA-FBA/PEI hydrogel (D-PFP). The D-PFP hydrogel was characterized using various techniques. The results indicated that the optimal conditions for hydrogel preparation involved using PF-0.25 polymer, which had an aldehyde group content of 0.82 mmol/g, as the precursor, along with a 12 wt% precursor solution for crosslinking with a 5 wt% PEI solution. The resulting hydrogel exhibited good structural stability and favorable morphology. Drug release studies indicated that the hydrogel demonstrated minimal drug leakage under physiological conditions (pH 7.4), while exhibiting a significantly higher drug release rate at pH 6.8, thereby underscoring its superior pH sensitivity. Rheological evaluations further confirmed its injectability and self-healing properties. Moreover, the hydrogel displayed excellent cytocompatibility and significantly inhibited cancer cell activity at pH 6.8. These characteristics suggest the potential of this hydrogel as a drug delivery system with ultra-sensitive drug release properties, particularly for future applications in chemotherapy for cancer. [Display omitted]